Heterogeneous Catalytic Conversion of Citronellal into Isopulegol and Menthol: Literature Review - Amri Yahya; Dwiarso Rubiyanto; Is Fatimah (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
The conversion of citronellal into isopulegol is a key route in the production of a number of important chemicals. In the perspective of green conversion, the use of a heterogeneous catalyst is superior due to its ease in separation and reusability, so it facilitates a highly economical conversion. In this review, we examine the use of some transition metals in cyclization reactions, which are suitable for citronellal conversion into isopulegol, and consider the potential progress in clay-based catalysts. The structure of clay which potentially provides the porosity by modification and supporting active metal is proposed to be the low-cost catalyst for the conversion. As other mechanism by porous materials-supported metal, the porosity of clay support contributes to conduct thesurface adsorption mechanism and the Broensted acid supply, meanwhile the metal acts as active site for cyclization, and in the one-pot conversion into menthol, as both cyclization and hydrogenation.